Karo during the Revolution, 1945-1949 - Arkini Sabrina; Budi Agustono; Nuhung Nuhung (History Department, Semarang State University and Historian Society of Indonesia, 2023)
The people joyfully welcomed the proclamation of independence that echoed through Tanah Karo. However, the independence was tested by the arrival of Dutch colonialists who sought to re-establish themselves. This study aims to explain the emergence of the nationalism movement in Tanah Karo and the development of the idea of nationalism during the revolutionary period that filled the movement. This research uses the historical method, which consists of heuristics, source criticism, interpretation and historiography. The sources used are archival documents, interviews, contemporary newspapers, and other sources relevant to this study. The results showed that the emergence of the nationalism movement was brought by Karo intellectuals who were members of the PNI. They came from economically well-established families and studied in Medan. The youth from Karo played an essential role in building the spirit of nationalism as a driving force in the people's struggle against the Dutch colonialists who sought to regain power. The transmission of the idea of nationalism was brought to Tanah Karo through media in the form of writings, speeches, training, learning and other things that aroused the passion of the people's resistance. Meanwhile, in the dynamics of the movement carried out through the spread of ideas of nationalism, there was a conflict between the ranks of the struggle, which could then be reduced by strategizing the struggle because there was a fear that the enemy would use the atmosphere.Proklamasi kemerdekaan menggema hingga ke Tanah Karo disambut rakyat dengan gembira namun sebagai upaya mempertahankan kemerdekaan dengan kedatangan kolonial Belanda yang ingin berkuasa. Studi ini bertujuan untuk menjelaskan kemunculan pergerakan dan berkembangnya gagasan nasionalisme di Tanah Karo. Penelitian ini menggunakan metode sejarah yang terdiri dari heuristik, kritik sumber, interpretasi dan historiografi. Sumber yang digunakan adalah sumber arsip, dokumen, wawancara, surat kabar sezaman, dan yang relevan dengan studi ini. Hasil penelitian yakni kemunculan pergerakan nasionalisme dibawa oleh kaum intelektual Karo. Mereka berasal dari keluarga yang mapan secara ekonomi dan menempuh pendidikan di Medan. Peran para pemuda Karo dalam membangun semangat nasionalisme sebagai motor penggerak perjuangan rakyat dalam menghempang kolonial Belanda yang ingin berkuasa kembali. Transmisi gagasan nasionalisme dibawa melalui media-media berupa tulisan, pidato, pelatihan, pembelajaran dan hal lainnya yang membangkitkan gairah perlawanan rakyat. Sementara itu dinamika pergerakan yang dilakukan melalui penyebaran ide-ide nasionalisme sempat menuai konflik antar barisan perjuangan yang kemudian dapat diredam dengan menyusun strategi perjuangan, hal ini karena terdapat rasa khawatir suasana tersebut dimanfaatkan oleh musuh.